Faktor-Faktor Yang Memengaruhi Status Gizi Anak Balita di Desa Waimital Kabupaten Seram Bagian Barat - Rumfot, Siti N R; Mailoa, Meity C; Augustyn, Gelora H (Universitas Pattimura, 2025)
The nutritional health of young children often mirrors the overall nutritional condition of a community. When the body lacks sufficient nutrients, it can lead to various health issues related to nutrition. These issues are classified into two categories: malnutrition, which arises when the body does not receive enough nutrients, and severe malnutrition, which is a more critical state resulting from significant nutrient deficiencies. This research seeks to explore the factors that affect the nutritional status of young children in Waimital Village, West Seram Regency. The study specifically targets children aged 21 to 48 months, with data gathered from local health posts and households. The factors considered in this study include household characteristics such as the mother's education, family income, family size, maternal knowledge of nutrition, and parenting practices. The findings reveal that the key factors affecting the children's nutritional status in the village include the mother’s education, her understanding of nutrition, parenting approaches, and the family's income level. However, the number of family members was found to have no significant impact on the children's nutritional status in the village.